Predicting Student Dropout Rates at Higher Degree Using Machine Learning and Dimensionality Reduction - Bezerra, Wanessa S.; Vale, Karliane M. O.; Gorgônio, Flavius L.; Guerra, Fabrício V. A.; Gorgônio, Arthur C.; Canuto, Anne M. P. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
This study proposes four indices for predicting student dropout in a computing course at a higher education institution, using machine learning (ML) and dimensionality reduction. Ten classification algorithms were applied to three datasets, including versions with and without the proposed indices. The best performance was achieved by QDA. SHAP analysis highlighted persistence and number of enrollments as the most relevant predictors.